Isolation and Molecular Characteristics of a CIAV Isolate From Pigeons, China - Shao, Hongxia; Li, Jinzhi; Yuan, Huisha; Ji, Lifei; Zhang, Jun; Jin, Wenjie; Qian, Kun; Ye, Jianqiang; Qin, Aijian (Frontiers in Veterinary Science, 2021)
Chicken infectious anemia virus (CIAV) mainly infects chickens and causes immunosuppression. In this study, a CIAV isolate, designated as Pigeon-CIAV-1906, was efficiently isolated from two sick pigeons by inoculating the samples into MSB1 cells. The genome of Pigeon-CIAV-1906 was amplified by PCR and analyzed. The genome size of Pigeon-CIAV-1906 was 2298 bp with the highest homology (99.5%) to Jilin strain (JL14023) and the lowest homology (91.5%) to Brazil strain (KY024579), which phylogenetically clustered into Group A. Notably, several amino acids such as 139K and 394Q related with high virulence were found in the VP1 of Pigeon-CIAV-1906. The isolation of Pigeon-CIAV-1906 and its molecular characteristics provide evidence for the cross-transmission of CIAV from chicken to pigeon and give novel insights into the molecular epidemiology of CIAV.